2022
DOI: 10.3390/epidemiologia3040033
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risks Factors Associated with Coxiella burnetii Infection in Slaughterhouse Zebu Cattle (Bos indicus) from Northern Regions of Cameroon

Abstract: A study was conducted to determine the seroprevalence and risks factors of Coxiella burnetii in zebu cattle from the northern regions of Cameroon. From a total of 2016 (1754 females and 262 males) sera sampled, 801, 762 and 453 were collected, respectively, from Adamawa, North and Far North, and screened for Coxiella burnetii using indirect enzyme-linked immunosorbent assay (iELISA). A total of 23.76% (479/2016) were serologically positive. The seroprevalence of Adamawa, North and Far North were 29.09% (233/80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
1
Order By: Relevance
“…Since we only sampled cattle in our study, we could not determine prevalence variation by animal species, and we also did not document any cattle housing system; however, the seroprevalence data inthe current study shows that the cattle in the study area are exposed to Coxiella burnetii with prevalence comparable to other studies (34). However, other studies, have shown that prevalence varies according to animal species (35, 36).…”
Section: Discussioncontrasting
confidence: 50%
“…Since we only sampled cattle in our study, we could not determine prevalence variation by animal species, and we also did not document any cattle housing system; however, the seroprevalence data inthe current study shows that the cattle in the study area are exposed to Coxiella burnetii with prevalence comparable to other studies (34). However, other studies, have shown that prevalence varies according to animal species (35, 36).…”
Section: Discussioncontrasting
confidence: 50%